THE IMPACT OF LOCAL TAXES AND FEES ON THE FORMATION OF THE RESOURCE POTENTIAL OF TERRITORIAL COMMUNITIES IN LVIV REGION (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The financial capacity of territorial communities plays a crucial role in the successful execution of the powers delegated to them within the framework of decentralization reform in Ukraine. As local self-government bodies gain greater autonomy and assume expanded responsibilities, the issue of securing adequate financial resources becomes increasingly important. Local taxes and fees constitute the primary source of revenue for community budgets. However, the efficiency of generating such revenues largely depends on various determinants, including population size, level of economic activity, geographic location, and the legal and regulatory framework. A thorough examination of these factors is essential for understanding the communities' potential to achieve financial self-sufficiency.Purpose of the Study. The purpose of this article is to analyze the theoretical and methodological foundations for the formation of financial resources in territorial communities, with particular emphasis on the role of local taxes and charges. Special attention is given to the impact of legislative changes on the fiscal capacity of communities and to the specific features of revenue generation in local budgets across Lviv region, taking into account the size and location of each community.Research Methods. The study employs a combination of general scientific and specialized methods. Theoretical analysis was used to examine current academic literature related to fiscal decentralization and local finance. Legal and regulatory analysis allowed for the assessment of changes in tax legislation and their implications for local tax administration. Statistical methods and data grouping techniques were applied to generalize revenue indicators across communities in Lviv region. Spatial analysis was also used to identify the influence of geographic factors on the effectiveness of local tax collection.Research Results. Current legislation provides communities with the authority to regulate local tax rates within defined boundaries, enabling a degree of financial flexibility. Nevertheless, the level of practical implementation of these powers remains uneven across regions. The findings indicate that communities within Lviv region differ significantly in terms of their ability to efficiently mobilize local tax revenues. The most favorable outcomes are observed in municipalities situated near the regional center, largely due to better infrastructure, higher business activity, and proximity to labor markets. In contrast, more remote and rural communities tend to show lower fiscal returns and greater dependence on intergovernmental transfers. It was also found that larger communities possess more developed administrative and institutional capacity, which facilitates more effective tax management. Meanwhile, abrupt or frequent changes in tax legislation-especially without adequate transitional periods-create obstacles for local budget planning.Conclusions. The formation of financial resources within territorial communities is shaped by a complex interaction of internal and external factors. Local taxes serve as a cornerstone of community revenue generation; however, their effective administration depends on such variables as community size, geographic position, and institutional capabilities. The study reveals substantial untapped potential in terms of increasing local tax revenues, particularly in rural areas. To enhance financial sustainability, it is necessary to improve tax administration practices, strengthen the human resources of local governments, and ensure greater predictability in the tax and regulatory environment.
Keywords: decentralization reform, local taxes and fees, resource potential of territorial communities.